2015
DOI: 10.1016/j.colsurfb.2014.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional drug nanocarriers formed by cRGD-conjugated βCD-PAMAM-PEG for targeted cancer therapy

Abstract: Polyamidoamine (PAMAM) dendrimer was conjugated with both carboxymethyl-β-cyclodextrin (βCD) and poly(ethylene glycol) (PEG). Cyclic RGD peptide, used as a tumor targeting ligand, was then selectively conjugated onto the distal ends of the PEG arms. The resulting βCD-PAMAM-PEG-cRGD polymer was able to form stable and uniform nanoparticles (NPs) in aqueous solution. Doxorubicin (Dox), a model hydrophobic anticancer drug, was effectively encapsulated in the NPs via an inclusion complex formed between the drug an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…In addition, Dox-encapsulated nanoparticles formed by poly(RGD- co -β-amino ester) and Dox-polymeric nanoparticles functionalized with RGD had higher cytotoxicity than nanoparticles prepared without RGD in U87MG cells [ 24 ]. Besides these, in recent years, other authors have described the improvement in transport of Dox into tumor cells with targeting of RGD-nanoparticles using different materials and methods of preparation [ 37 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Dox-encapsulated nanoparticles formed by poly(RGD- co -β-amino ester) and Dox-polymeric nanoparticles functionalized with RGD had higher cytotoxicity than nanoparticles prepared without RGD in U87MG cells [ 24 ]. Besides these, in recent years, other authors have described the improvement in transport of Dox into tumor cells with targeting of RGD-nanoparticles using different materials and methods of preparation [ 37 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 The Arg-Gly-Asp (RGDyC) is selective to α v β 3 integrin peptides and can also combine with integrin receptors on the surface of leukocytes (neutrophils and monocytes). 25,26 It has been found that both α v β 3 and α v β 5 integrins are expressed on glioma cells and vasculature. 27,28 It provides an ideal strategy for targeted delivery.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify cumulative drug released at each time point, the absorbance of collected aliquots was assessed at 485 nm wavelength using a plate reader, and compared to a DOX standard curve. 29, 64 Peak absorbance of DOX in PBS (pH 7.4) was previously confirmed to be 485 nm when assessed using an absorbance spectral sweep from 300–700 nm at 1 mg/mL concentration (Supplemental Figure 1). …”
Section: Methodsmentioning
confidence: 73%